2019
DOI: 10.4251/wjgo.v11.i4.335
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HER2 protein expression and HER2 gene amplification in colorectal adenocarcinomas

Abstract: BACKGROUND Human epidermal growth factor receptor 2 (HER2) is an oncogenic driver, and a well-established therapeutic target in breast and gastric cancers. While the role of HER2 as a prognostic biomarker in colorectal adenocarcinomas (CRCs) remains uncertain, its relevance as a therapeutic target has been established. We undertook the present study to evaluate the frequency of HER2 expression in CRC and to correlate it with various clinicopathological variables. AIM To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
1
27
0
3
Order By: Relevance
“…The number of studies suggests that HER2 may play some role in tumor progression and would be a valuable prognostic factor for CRC patients (Laurentpuig et al, 2016;Stahler et al, 2017). But in other studies, HER2 gene amplification was higher in patients with more advanced stage or distant metastases, and no significant difference in prognosis for CRC patients (Pietrantonio et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The number of studies suggests that HER2 may play some role in tumor progression and would be a valuable prognostic factor for CRC patients (Laurentpuig et al, 2016;Stahler et al, 2017). But in other studies, HER2 gene amplification was higher in patients with more advanced stage or distant metastases, and no significant difference in prognosis for CRC patients (Pietrantonio et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…The different criteria of membrane positivity may also cause for the conflicting results, Liu et al (2019) argued HER2 status evaluated by the HERACLES criteria showed survival predictive for stage II-III CRC, but the results were not represented based on the GEA diagnostic criteria. In present study, the GEA criteria was used, and 33.3% (18/54) samples with IHC staining 2+ were confirmed to harbor HER2 gene amplification, but Wang et al (2019) judged only 20% of tumors with HER2 IHC 2+ staining showing gene amplification based on this criteria. IHC is a semiquantitative method and may be influenced by subjective perception of pathologists frequently, so exactly HER2 positive standardized by IHC in CRC is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, 5FU-SLN 4 activity in mouse bearing HCT-116 subcutaneous tumor significantly inhibited the HER2 expression. In literature, HER2 overexpression or amplification has been implicated as one of the drivers in CRC progression 34,35 . But further investigation of 5FU-SLN 4 's biodistribution in vivo needs to be carried out to fully determine its pattern of distribution in tissues relative to tumor tissue.…”
Section: Resultsmentioning
confidence: 99%
“…C max , peak plasma concentration; T max , peak time; AUC (0 − t) , area under the plasma concentration-time curve; MRT, mean residence time; k 10 , elimination rate constant; Cl, clearance; V d , volume of distribution; k a , absorption rate constant (Data analyzed using unpaired t-test, two-tailed). www.nature.com/scientificreports/ eral solid tumors including CRC [34][35][36] . These receptors are frequently reported to harbor aberrant activities that lead to the proliferation, survival, migration and differentiation required for CRC pathogenesis.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…However, in the report described by Wang et al . 39 , 11.8% (12/102) of CRCs with HER2 IHC scores of 2+ and in 82.8% (24/29) of CRCs with HER2 IHC scores of 3+ were identified as HER2 amplification. One explanation for these differences may be that antibodies used for IHC or positive criteria for FISH varied among research groups.…”
Section: Discussionmentioning
confidence: 99%